Функціональні матеріали з пам’яттю форми: сучасний стан і перспективи використання (за матеріалами наукової доповіді на засіданні Президії НАН України 21 березня 2018 р.) - Фірстов, Г.С. (Вісник НАН України, 2018)
Доповідь присвячено дослідженням функціональних матеріалів з пам’яттю
форми. Зазначено, що промислові сплави з пам’яттю форми мають низку
недоліків, а їх застосування в медицині гальмується насамперед їх неповною біосумісністю. В Інституті металофізики ім. Г.В. Курдюмова НАН
України вперше було створено новітній клас функціональних матеріалів —
високоентропійні сплави з пам'яттю форми, які мають поліпшені фізико-механічні характеристики, що дозволяє вийти на новий рівень їх використання не лише в автобудівній, авіакосмічній, енергетичній та видобувній
галузях індустрії, а й, що найважливіше, у медичній сфері. An overview of the scientific direction devoted to the study of shape memory functional materials has been presented.
The special role played by Ukrainian scientists in its founding and development in the world was emphasized. It is noted
that shape memory alloys such as nitinol or copper-based alloys can not be used at elevated temperatures, and so-called
high-temperature shape memory alloys have a number of disadvantages, which are mainly related to relaxation processes
of internal stresses through plastic deformation and diffusion processes. Medical applications of industrial shape memory
alloys are restricted by incomplete biocompatibility. The ways of improvement of alloys with memory of the form through
the resistance of forms of degradation, thermal, mechanical, functional fatigue, etc. are analyzed. It is shown that it is the
materials with AS / Tmelt not greater than 0.4, with low symmetry of the high-temperature phase, with the essential
strengthening are the best for high temperature alloys application. At present, such properties as significant strengthening
and slow diffusion are characteristic of the novel structural materials — highly-entropy alloys, which by definition
have high stability. In the Kurdyumov Institute for Metal Physics for the first time high values of the yield strength twice
as high as for nitinol and the possibility of martensitic transformation and corresponding memory behavior was combined
in high-entropy intermetallic compounds. It was concluded that new class of functional materials — high entropy
shape memory alloys has been created. It will be possible not only to reach a new level of their application in the automotive,
aerospace, energy or mining industries, but, most importantly, to deepen their medical application.